Parametric design and evaluation of TPMS-like cellular solids. (September 2022) - Jones, Alistair; Leary, Martin; Bateman, Stuart; Easton, Mark
Graphical abstract: Highlights: Presents a formal process for designing and generating CAD models with TPMS-like topology, including a structured set of design parameters. Presents various rapid analysis techniques and metrics for assessing the performance of cellular solids. Quantifies and characterises key relationships between design parameters and performance metrics. Presents an example of using the metrics to assess suitability of a structure for laser powder bed fusion. Abstract: Triply periodic minimal surfaces (TPMS) present a starting point for designing infinitely many novel cellular solids, creating the need for a structured approach to their design and evaluation. In this study the design space is formalised using a set of input parameters and evaluation metrics to provide a structured and reproducible approach to designing a TPMS-like cellular solids. Interactions between the design parameters and evaluation metrics are identified using a full-factorial design of experiments. From this the most impactful design parameters are identified as the TPMS equation, type of structure, and volume fraction. It was found that the gyroid-surface structure provided the most flexibility, with near-isotropic mechanical properties across a wide range of volume fractions, allowing the creation of reduced mass/stiffness designs without introducing anisotropy or variation in Poisson's ratio. The volume fraction at which the connectivity of a structure changes, "pinch-off limits" are presented for six of the most commonly investigated TPMS-like cellular solids. Additionally, the effects of common transformations are presented including: examples of how phase-shift and/or rotation can be used to modify the features which intersect the free-boundary of a design; dimensional analysis which shows the practical effects changing unit cell size; and analysis showing the effect of rotating a cellular structure on both the mechanical properties and surface orientation. These computational studies are supported with a physical case study which demonstrates how several design parameters may be modified to change the manufacturability of a TPMS-like cellular solid.